Prototype of Vehicle Condition Monitoring System for the Adev 01 Monalisa Electric Car - Wibisono, Muhammad Damar; Ma'arif, Alfian (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
The monitoring system used in electric cars is a vehicle condition display where the vehicle has a main drive in the form of a BLDC hub motor and a PSMS type controller. The aim of this research is to measure the temperature of the controller using a temperature sensor (DS18b20), measure battery voltage using a series of resistors, current sensor using ACS712. The input used is the sensor input which is used to detect a condition or physical change which is required in the system output. Arduino Uno R3 hardware is used to receive, manage and provide electrical signals. A user interface or user interface device is needed so that the operation of the system can be known. In this experiment, a Nextion LCD was used as a user interface. The reading tests that have been carried out produce quite varied responses, but are still within normal limits. This shows that the tests carried out have been successfully carried out well. As a result, the tool created can display data accurately, with the display data being displayed at all times as long as the power supply receives power input. The ADEV 01 Monalisa electric car vehicle condition monitoring system prototype was designed and made with smart technology which can later be developed properly and can be used to produce good and precise displays. By experimenting with the vehicle in a stationary condition, the average difference produced in the battery voltage data shows a difference of 0.284 V, in the current data using the instrument it shows a difference of 0.622 mA, in the controller temperature data it shows a difference of 1.24 ℃, with the experiment in the condition of the vehicle in speed conditions low, the average difference produced in the battery voltage data shows a difference of 0.245 V, in the current data for the instrument it shows a difference of 0.183 mA, in the controller temperature data it shows a difference of 0.074 ℃, with experimental conditions of the vehicle in high speed conditions the average difference produced in The battery voltage data shows a difference of 0.083 V, the instrument current data shows a difference of 0.79 mA, the controller temperature data shows a difference of 1.192 ℃.